Pengaruh Kepercayaan, Kemudahan dan Persepsi Risiko Terhadap Keputusan Pembelian Menggunakan Aplikasi Pinjaman Online Akulaku - Susanty, Shanty; Indrayani, Luh (Fakultas Ekonomi Universitas Pendidikan Ganesha, 2024)
This study aims to examine: (1) the influence of trust on purchasing decisions using the Akulaku online loan application in the village of Kajanan, (2) the influence of convenience on purchasing decisions using the Akulaku online loan application, (3) the influence of risk perception on purchasing decisions using the Akulaku online loan application and (4) the influence of trust, convenience and risk perception on purchasing decisions using the Akulaku online loan application. This type of research is quantitative research. The population in this study is the community using the Akulaku online loan application in the village of Kajanan village. The population size in this study is unknown because there is no exact data on the number of Akulaku users in Kajanan village. The number of samples was 125. The sample technique used is the purposive sampling technique. The data collection method uses questionnaires with data analysis methods, namely multiple linear regression analysis. Hypothesis Test using t test and F test processed with the help of SPSS 25 for windows. The results of this study show that: (1) trust has a positive and significant effect on purchasing decisions using Akulaku in the village of Kajanan with a significant value of 0,005<0.05, (2) ease has a positive and significant effect on purchasing decisions using Akulaku in the village of Kajanan with a significant value of 0,014<0.05 (3) risk perception has a positive and significant effect on purchasing decisions using Akulaku in kajanan village villages with a significance value of 0.008<0.05 and (4) trust, convenience and risk perception have a positive and significant effect on purchasing decisions using Akulaku in kampung kajanan village with a significant value of 0.001<0.05.